Acousto-optical modulation of light at a doubled sound frequency. (February 2016) - Kotov, V.M.; Averin, S.V.; Shkerdin, G.N.
Abstract: A method of acousto-optical (AO) Bragg diffraction is proposed that provides the amplitude modulation of optical radiation at a doubled acoustic frequency. The method is based on the double transmission of the light through the AO modulator made of a gyrotropic crystal and is experimentally tested by the example of the modulation of light with a wavelength of, controlled by the paratellurite AO cell.